A Meningkatkan Kemampuan Operasi Pengurangan pada Siswa Tunagrahita dengan Media Karbicus - Neny Yuniarti; Yohanes Subasno (Jurnal Pelayanan Pastoral, 2023)
The difficulty experienced by students with mental disabilities in understanding the learning of reduction operations is due to their very limited learning capacity, especially regarding abstract matters. Students need concrete and interesting media so that the learning process is more fun and easy to understand, so karbicus media (Cuisenairare number cards) are offered. The purpose of the study was to determine the influence of karbicus media on improving students' abilities in learning mathematics material of 1-10 reduction operations in class IV SLB YPAC MALANG CITY. This research method is classroom Action research. This study was designed in 2 cycles, each cycle consists of 3 meetings. Each cycle consists of several stages, namely planning, implementation, observation, and reflection. Data were collected by test and observation techniques. Indicators for students are declared complete learning when they reach a score of 70 or more and are declared to increase when the post-test value of cycle II is higher than the post-test value of cycle I. The results of the study can be concluded that there is an increase in the ability of mentally impaired students in class IV SLB YPAC MALANG IN the 1-10 summation material using karbicus media.